Trends in the architecture of Kovel in the interwar period - Abramiuk, Inna (Theory and practice of design, 2022)
The purpose of preparing the material arose from the need for a comprehensive study of trends in the architecture of the Volyn city of Kovel, as an example of architectural and spatial development of small towns in the 20-30s of the twentieth century. Being in the 20-30s of the twentieth century аn important transport and military-administrative center, Kovel, despite the status of a small town, attracted attention as a socio-cultural center, whose architectural development was characterized by multi-vector and focus on the comfort of residents. It is established that since 1920, Kovel together with the whole of Volyn became part of the Polish state and received the status of a county town of Volyn Voivodeship. Since then, the active development of urban architecture began, which has become a symbol of modernity, along with the spatial development of the city, aimed at streamlining and increasing the level of its comfort. It was found that Kovel’s inclusion in the avant-garde direction of the state’s architectural development took place through the development of important city objects by architects from Warsaw, Lublin and Lutsk, including Stefan Schiller, Volodymyr Winkler, Josef Shanaitz, Bohdan Lachert, Wladyslaw Stachon and others. It was found that in a short period of twenty years of history, there were significant changes in the architectural and spatial structure of Kovel, which reflected two global stylistic trends: traditionalism and avant-garde. Buildings appeared in the city, representing the features of “courtyard” traditional architecture, neo-Gothic style and a combination of neoclassicism with simple volumes of modernism. Following detailed research of Kovel’s architecture and its popularization will allow to preserve the common Ukrainian-Polish heritage and develop concepts of city development taking into account the value of traditions, without destroying the aesthetic integrity of the environment of historically formed areas.